A low-temperature toughened and modified PC composite material and preparation method thereof

By adding a Silicon co-polymerization PC in the PC composite material to add a specific siliconxane chain segment, the problem of the existing PC composite materials in the extremely cold environment has achieved the decline in impact performance, and the efficient and tougher in -40 ° C environment is realized. Effect.

CN117645782BActive Publication Date: 2025-01-28XINXING JIHUA (BEIJING) MATERIAL TECH RES INST CO LTD
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202311611915.1
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-11-29
Publication Date
2025-01-28
Estimated Expiration
2043-11-29

AI Technical Summary

Technical Problem

The impact resistance of existing PC composites has significantly decreased in extreme cold environments, resulting in limited application under low temperature conditions.

Method used

By adding a silicon -co -polymer PC in a specific polysiliconxane chain segment to the PC composite material, the quality ratio of the resin is adjusted, the silicane content is improved, and the PC phase is improved.

Benefits of technology

It significantly improves the low temperature impact impact performance of PC composite materials in the -40 ℃ environment, and meets the application needs of extremely cold areas.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0004576982410000051
    Figure BDA0004576982410000051
  • Figure BDA0004576982410000061
    Figure BDA0004576982410000061
Patent Text Reader

Abstract

The present invention discloses a low-temperature toughened and modified PC composite material and a preparation method thereof. The PC composite material is made of the following components in mass percentage: 66.33% of siloxane copolymerized polycarbonate resin, 32.67% of polycarbonate resin, 0.3% of anti-dripping agent, 0.2% of antioxidant, 0.1% of light stabilizer, and 0.4% of other additives; wherein the polycarbonate is A2100; the siloxane copolymerized polycarbonate resin is CH9115, and the average domain size of its polysiloxane chain segment is 20 to 45nm; in the entire compound system, the siloxane content is 3.96%. The present invention adds a silicon copolymerized PC with an average domain size of a specific polysiloxane chain segment to PC, and adjusts the mass ratio of the two resins to adjust the siloxane content of the PC composite material to a specific value, thereby achieving efficient toughening of the PC phase. Compared with conventional addition of toughening agents, the silicon copolymerized PC has good compatibility with polycarbonate, thereby ensuring that it exerts an excellent toughening effect at low temperatures.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of materials, and particularly relates to a low-temperature toughened and modified PC composite material and a preparation method thereof. Background Art

[0002] Polycarbonate (PC) is a thermoplastic engineering plastic containing carbonate groups in the molecular chain, with a wide molecular weight distribution, usually 32,000 to 115,000. PC is an amorphous resin that is not easy to crystallize, has good heat resistance and low temperature resistance, has good mechanical properties, electrical properties, flame retardant properties and dimensional stability in a wide temperature range, and can be used for a long time at -40 to 125°C. However, the existing PC composite materials have weak low temperature resistance and are prone to microscopic tearing, causing molecular chain breakage and product cracking, which seriously limits the application of PC composite materials.

[0003] PC composite materials are widely used in the fields of automobiles, medical treatment, communication electronics, etc. However, the impact resistance of existing PC composite materials in extremely cold environments is significantly reduced, which greatly limits their application in low temperature conditions. At present, the main method used is modification to solve the brittle fracture problem of PC materials in a -40℃ environment. Summary of the invention

[0004] In order to overcome the problem that the existing PC composite materials have poor low-temperature cracking resistance, the purpose of the present invention is to provide a low-temperature toughened and modified PC composite material and a preparation method thereof, which can significantly improve the low-temperature impact resistance of the PC composite material in an environment of -40°C (altitude cold areas) while ensuring the original physical and chemical properties of the PC composite material, so as to meet the application requirements of various shell materials in extremely cold areas.

[0005] The low-temperature toughened and modified PC composite material provided by the present invention is made of the following components in percentage by mass: 66.33% of siloxane copolymerized polycarbonate resin, 32.67% of polycarbonate resin, 0.3% of anti-dripping agent, 0.2% of antioxidant, 0.1% of light stabilizer, and 0.4% of other additives;

[0006] Wherein, the polycarbonate is A2100;

[0007] The siloxane copolymer polycarbonate resin is CH9115, with a relative molecular weight of 24,000, an average domain size of the polysiloxane chain segment of 20 to 45 nm, and a mass melt flow rate of 9 to 12 g / 10 min at 300° C. / 1.2 kg;

[0008] In the whole compound system, the content of siloxane is 3.96%.

[0009] The anti-dripping agent is a coated modified polytetrafluoroethylene powder, specifically one of FD3150 and FR3306;

[0010] The antioxidant is a compound of a hindered phenol antioxidant (specifically, antioxidant 1076) and a phosphite antioxidant (specifically, antioxidant 168);

[0011] The light stabilizer is one or a mixture of UV637 and UV981, specifically a compound of UV637 and UV981, with a compound weight ratio of 1:1;

[0012] The other auxiliary agent is navy blue toner.

[0013] Specifically, the antioxidant is a compound of antioxidant 1076 and antioxidant 168 in a weight ratio of 1:1;

[0014] The light stabilizer is a compound of UV637 and UV981 in a weight ratio of 1:1;

[0015] The anti-dripping agent is FD3150.

[0016] The above-mentioned low-temperature toughened and modified PC composite material is prepared by a method comprising the following steps:

[0017] (1) Substrate treatment: After drying the siloxane copolymerized polycarbonate resin and the polycarbonate resin at 130° C. for 4 h and the auxiliary agent at 80° C. for 2 h, the polycarbonate and siloxane copolymerized polycarbonate resin were weighed in proportion and added to a high-speed mixer. The speed was set to 300 to 500 rpm / min and the mixture was fully mixed for 3 to 5 min until uniform.

[0018] (2) Raw material stirring: add an anti-dripping agent, an antioxidant, a light stabilizer and other additives, set the rotation speed to 100 to 300 rpm / min, mix for 4 minutes, and obtain a mixture.

[0019] (3) Extruder preset: The pellet forming barrel temperature of the pelletizer is divided into nine temperature zones, and the specific temperature control of each zone is as follows: Zone 1: 230°C-250°C, Zone 2: 240°C-260°C, Zone 3: 250°C-270°C, Zone 4: 250°C-270°C, Zone 5: 250°C-270°C, Zone 6: 240°C-260°C, Zone 7: 230°C-250°C, Zone 8: 230°C-250°C, Zone 9: 240°C-260°C, die head: 235-245°C; main engine speed is 250-350rpm; pelletizing speed is 350-400rpm;

[0020] (4) Extrusion granulation: The mixed material of step (2) is added into the above-mentioned preset extrusion granulator, and the processing temperature is controlled between 230°C and 270°C. The mixture is melt-extruded, wire-drawn, cooled, air-dried, and pelletized to obtain a uniform low-temperature toughened and modified PC composite material.

[0021] Compared with the prior art, the present invention has the following advantages:

[0022] The present invention adds a silicon copolymer PC having an average phase domain size of a specific polysiloxane segment to PC, and adjusts the mass ratio of the two resins to adjust the siloxane content of the PC composite material to a specific value, thereby achieving efficient toughening of the PC phase. Compared with conventional addition of toughening agents, the silicon copolymer PC has good compatibility with polycarbonate, thereby ensuring that it exerts an excellent toughening effect at low temperatures. DETAILED DESCRIPTION

[0023] The present invention is further described in detail below in conjunction with specific embodiments, and the examples provided are only for illustrating the present invention, rather than for limiting the scope of the present invention. The examples provided below can be used as a guide for further improvements by those of ordinary skill in the art, and do not constitute a limitation of the present invention in any way.

[0024] The experimental methods in the following examples, unless otherwise specified, are all conventional methods, and are performed according to the techniques or conditions described in the literature in the art or according to the product instructions. The materials, reagents, etc. used in the following examples, unless otherwise specified, can all be obtained from commercial channels.

[0025] Example 1. Preparation of low temperature toughened modified PC composite material

[0026] The PC composite material is composed of the following materials in weight percentage: 66.33% of siloxane copolymerized polycarbonate resin, 32.67% of polycarbonate resin, 0.3% of anti-dripping agent, 0.2% of antioxidant, 0.1% of light stabilizer, and 0.4% of other additives;

[0027] Wherein, the polycarbonate is bisphenol A type aromatic polycarbonate, purchased from Wanhua Chemical A2100;

[0028] The siloxane copolymer polycarbonate resin is a polycarbonate resin copolymerized by bisphenol A and siloxane, with a trade name of CH9115 (siloxane content 6%), purchased from Cangzhou Dahua Company, with a relative molecular weight of 24,000, an average domain size of the polysiloxane chain segment of 20 to 45 nm, and a mass melt flow rate of 9 to 12 g / 10 min at 300° C. / 1.2 kg;

[0029] The antioxidant is a compound of antioxidant 1076 and antioxidant 168 in a weight ratio of 1:1;

[0030] The light stabilizer is a compound of UV637 and UV981 in a weight ratio of 1:1;

[0031] The anti-dripping agent is FD3150;

[0032] The other auxiliary agent is navy blue toner.

[0033] In the whole compound system, the content of siloxane is 3.96%.

[0034] Preparation method:

[0035] (1) Substrate treatment: After drying the siloxane copolymerized polycarbonate resin and the polycarbonate resin at 130° C. for 4 h and the auxiliary agent at 80° C. for 2 h, the polycarbonate and siloxane copolymerized polycarbonate resin were weighed in proportion and added to a high-speed mixer. The speed was set to 350 rpm / min and the mixture was fully mixed for 4 min until uniform.

[0036] (2) Raw material stirring: add an anti-dripping agent, an antioxidant, a light stabilizer and other additives, set the rotation speed to 100 rpm / min, mix for 4 minutes, and obtain a mixture.

[0037] (3) Extruder preset: The pellet forming barrel temperature of the pelletizer is divided into nine temperature zones. The specific temperature control of each zone is as follows: Zone 1: 230°C, Zone 2: 240°C, Zone 3: 250°C, Zone 4: 250°C, Zone 5: 270°C, Zone 6: 260°C, Zone 7: 250°C, Zone 8: 250°C, Zone 9: 260°C, die head: 245°C; main engine speed is 250rpm; pelletizing speed is 350rpm.

[0038] (4) Extrusion granulation: The mixed material of step (2) is added into the above-mentioned preset extrusion granulator, and the processing temperature is controlled between 230°C and 270°C. The mixture is melt-extruded, wire-drawn, cooled, air-dried, and pelletized to obtain a uniform low-temperature resistant PC composite material.

[0039] Comparative Example 1: Preparation of PC composite material

[0040] The PC composite material comprises the following materials in weight percentage: 66.33% of siloxane copolymerized polycarbonate resin, 32.67% of polycarbonate resin, 0.3% of anti-dripping agent, 0.2% of antioxidant, 0.1% of light stabilizer, and 0.4% of other additives;

[0041] Wherein, the polycarbonate is bisphenol A type aromatic polycarbonate, purchased from Wanhua Chemical A2100;

[0042] The siloxane copolymer polycarbonate is Wanhua Chemical 2240T (siloxane content 6%), with a molecular chain length of 5-15 nm and a mass melt flow rate of 9-13 g / 10 min at 300° C. / 1.2 kg;

[0043] The antioxidant is a compound of antioxidant 1076 and antioxidant 168 in a weight ratio of 1:1;

[0044] The light stabilizer is a compound of UV637 and UV981 in a weight ratio of 1:1;

[0045] The anti-dripping agent is FD3150;

[0046] The other auxiliary agent is navy blue toner.

[0047] In the whole compound system, the content of siloxane is 3.96%.

[0048] Preparation method:

[0049] (1) Substrate treatment: After drying the siloxane copolymerized polycarbonate resin and the polycarbonate resin at 130° C. for 4 h and the auxiliary agent at 80° C. for 2 h, the polycarbonate and siloxane copolymerized polycarbonate resin were weighed in proportion and added to a high-speed mixer. The speed was set to 350 rpm / min and the mixture was fully mixed for 4 min until uniform.

[0050] (2) Raw material stirring: add an anti-dripping agent, an antioxidant, a light stabilizer and other additives, set the rotation speed to 100 rpm / min, mix for 4 minutes, and obtain a mixture.

[0051] (3) Extruder preset: The pellet forming barrel temperature of the pelletizer is divided into nine temperature zones. The specific temperature control of each zone is as follows: Zone 1: 250°C, Zone 2: 260°C, Zone 3: 270°C, Zone 4: 270°C, Zone 5: 270°C, Zone 6: 260°C, Zone 7: 250°C, Zone 8: 250°C, Zone 9: 260°C, die head: 245°C; main engine speed is 300rpm; pelletizing speed is 350rpm.

[0052] (4) Extrusion granulation: The mixed material of step (2) is added into the above-mentioned preset extrusion granulator, and the processing temperature is controlled between 245°C and 270°C. The mixture is melt-extruded, wire-drawn, cooled, air-dried, and pelletized to obtain a uniform low-temperature resistant PC composite material.

[0053] Comparative Example 2: Preparation of low temperature toughened modified PC composite material

[0054] The PC composite material is composed of the following materials in weight percentage: 19.8% of siloxane copolymerized polycarbonate resin, 79.2% of polycarbonate resin, 0.3% of anti-dripping agent, 0.2% of antioxidant, 0.1% of light stabilizer, and 0.4% of other additives;

[0055] Wherein, the polycarbonate is bisphenol A type aromatic polycarbonate, purchased from Wanhua Chemical A2100;

[0056] The siloxane copolymer polycarbonate resin is a polycarbonate resin copolymerized by bisphenol A and siloxane, purchased from Wanhua Chemical under the trade name of 2060 (siloxane content 20%), with a relative molecular weight of 24,000, an average domain size of the polysiloxane chain segment of 30 to 60 nm, and a mass melt flow rate of 9 to 12 g / 10 min at 300° C. / 1.2 kg;

[0057] The antioxidant is a compound of antioxidant 1076 and antioxidant 168 in a weight ratio of 1:1;

[0058] The light stabilizer is a compound of UV637 and UV981 in a weight ratio of 1:1;

[0059] The anti-dripping agent is FD3150;

[0060] The other auxiliary agent is navy blue toner.

[0061] In the whole compound system, the content of siloxane is 3.96%.

[0062] Preparation method:

[0063] (1) Substrate treatment: After drying the siloxane copolymerized polycarbonate resin and the polycarbonate resin at 130° C. for 4 h and the auxiliary agent at 80° C. for 2 h, the polycarbonate and siloxane copolymerized polycarbonate resin were weighed in proportion and added to a high-speed mixer. The speed was set to 350 rpm / min and the mixture was fully mixed for 4 min until uniform.

[0064] (2) Raw material stirring: add an anti-dripping agent, an antioxidant, a light stabilizer and other additives, set the rotation speed to 100 rpm / min, mix for 4 minutes, and obtain a mixture.

[0065] (3) Extruder preset: The pelletizing barrel temperature of the pelletizer is divided into nine temperature zones. The specific temperature control of each zone is as follows: Zone 1: 240°C, Zone 2: 250°C, Zone 3: 250°C, Zone 4: 250°C, Zone 5: 260°C, Zone 6: 260°C, Zone 7: 260°C, Zone 8: 260°C, Zone 9: 270°C, die head: 245°C; main engine speed is 300rpm; pelletizing speed is 300rpm.

[0066] (4) Extrusion granulation: The mixed material of step (2) is added into the above-mentioned preset extrusion granulator, and the processing temperature is controlled between 240°C and 270°C. The mixture is melt-extruded, wire-drawn, cooled, air-dried, and pelletized to obtain a uniform low-temperature resistant PC composite material.

[0067] Comparative Example 3: Commercially available polycarbonate modified plastics

[0068] Sabic 9330

[0069] The comparison of main components and experimental results in the above examples and comparative examples are shown in Table 1-2 below:

[0070] Table 1 Main components of PC composite materials obtained in Examples and Comparative Examples

[0071]

[0072] The performance results of the obtained products are shown in Table 2.

[0073] Table 2. Main physical properties of PC composite materials obtained in Examples and Comparative Examples

[0074]

[0075]

[0076] Compared with the prior art, the present invention has the following advantages:

[0077] Based on the above, the advantage of the present invention is that, under the condition of consistent siloxy content, the siloxane copolymerized polycarbonate resin with an average domain size of polysiloxane segments in a specific range is compounded with the polycarbonate resin to effectively improve the low temperature resistance of the PC composite material at -40°C. Through the formulation of Example 1, the cantilever beam impact strength of the obtained polycarbonate modified plastic at -40°C reaches 734 J / m.

[0078] The present invention has been described in detail above. For those skilled in the art, without departing from the purpose and scope of the present invention, and without the need to carry out unnecessary experimental conditions, the present invention can be implemented in a wide range under equivalent parameters, concentrations and conditions. Although the present invention provides specific embodiments, it should be understood that the present invention can be further improved. In a word, according to the principles of the present invention, the application is intended to include any changes, uses or improvements to the present invention, including departure from the disclosed scope in the application, and changes made with conventional techniques known in the art.

Claims

1. A PC composite material, made of the following components in percentage by mass: 66.33% of siloxane copolymerized polycarbonate resin, 32.67% of polycarbonate resin, 0.3% of anti-dripping agent, 0.2% of antioxidant, 0.1% of light stabilizer, and 0.4% of other additives; in, The polycarbonate is Wanhua Chemical A2100; The siloxane copolymer polycarbonate resin is CH9115 from Cangzhou Dahua Company, with a relative molecular weight of 24,000, an average domain size of the polysiloxane chain segment of 20 to 45 nm, and a mass melt flow rate of 9 to 12 g / 10 min at 300° C. / 1.2 kg; In the whole compound system, the content of siloxane is 3.96%.

2. The PC composite material according to claim 1, characterized in that: The anti-dripping agent is coated modified polytetrafluoroethylene powder.

3. The PC composite material according to claim 2, characterized in that: The anti-dripping agent is one of FD3150 and FR3306.

4. The PC composite material according to claim 1, characterized in that: The antioxidant is a compound of a hindered phenol antioxidant and a phosphite antioxidant.

5. The PC composite material according to claim 1, characterized in that: The light stabilizer is one of UV637 and UV981 or a mixture of several thereof.

6. The PC composite material according to claim 1, characterized in that: The other auxiliary agent is navy blue toner.

7. The PC composite material according to claim 1, characterized in that: The antioxidant is a compound of antioxidant 1076 and antioxidant 168, with a compound weight ratio of 1:1; The light stabilizer is a compound of UV637 and UV981, and the compound weight ratio is 1:1; The anti-dripping agent is FD3150.

8. A method for preparing the PC composite material according to any one of claims 1 to 7, comprising the following steps: (1) Substrate treatment: After drying the siloxane copolymerized polycarbonate resin and the polycarbonate resin at 130° C. for 4 h and the additive at 80° C. for 2 h, weigh the polycarbonate and siloxane copolymerized polycarbonate resin according to the proportion, add them into a high-speed mixer, set the speed to 300-500 rpm, and mix thoroughly for 3-5 min until uniform; (2) Raw material stirring: add an anti-dripping agent, an antioxidant, a light stabilizer and other additives, set the speed to 100 to 300 rpm, mix for 4 minutes, and obtain a mixture; (3) Extruder preset: The pellet forming barrel temperature of the pelletizer is divided into nine temperature zones, and the specific temperature control of each zone is as follows: Zone 1: 230°C-250°C, Zone 2: 240°C-260°C, Zone 3: 250°C-270°C, Zone 4: 250°C-270°C, Zone 5: 250°C-270°C, Zone 6: 240°C-260°C, Zone 7: 230°C-250°C, Zone 8: 230°C-250°C, Zone 9: 240°C-260°C, die head: 235-245°C, main engine speed is 250-350rpm; pelletizing speed is 350-400rpm; (4) Extrusion granulation: The mixed material of step (2) is added into the above-mentioned preset extruder, and the processing temperature is controlled between 230°C and 270°C. The mixture is melt-extruded, wire-drawn, cooled, air-dried, and pelletized to obtain a uniform low-temperature toughened and modified PC composite material.

Citation Information

Patent Citations

  • Polycarbonate-polyorganosiloxane copolymer, preparation method and resin composition containing copolymer

    CN114196001A